2010
DOI: 10.1097/shk.0b013e3181ceede4
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside R1 Attenuates Renal Ischemia-Reperfusion Injury in Rats

Abstract: Ischemia-reperfusion (I/R) injury of the kidney is a complex pathophysiological process and a major cause of acute renal failure. It has been shown that I/R injury is related to inflammatory responses and activation of apoptotic pathways. Inhibition of certain elements of inflammatory responses and apoptotic pathway seemed to ameliorate renal I/R injury. As an effective element of Panax notoginseng, NR1 has antioxidant, anti-inflammatory, antiapoptotic, and immune-stimulatory activities. Therefore, we speculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…Rodriguez-Peña et al who explained that the initial pathological events in renal I/R include vasoconstriction, endothelial cell activation, tubular desquamation and swelling, necrosis of the tubular epithelium, and interstitial edema [17], giving way to the progression of the inflammatory process, a major cause of I/R-induced tissue injury [18,19]. The necrotic cells triggered by the lack of oxygen and nutrients in ischemic process can greatly stimulate immune responses and result in the infiltration of inflammatory cells and the production of cytokines [20].…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Peña et al who explained that the initial pathological events in renal I/R include vasoconstriction, endothelial cell activation, tubular desquamation and swelling, necrosis of the tubular epithelium, and interstitial edema [17], giving way to the progression of the inflammatory process, a major cause of I/R-induced tissue injury [18,19]. The necrotic cells triggered by the lack of oxygen and nutrients in ischemic process can greatly stimulate immune responses and result in the infiltration of inflammatory cells and the production of cytokines [20].…”
Section: Discussionmentioning
confidence: 99%
“…Panax notoginseng is believed to have anti-inflammatory, antioxidative, and antiapoptotic properties (Liu et al, 2010. In the study by Zhang et al (2015) study, NGR1 could attenuate inflammatory bowel disease via the pregnane X receptor.…”
Section: Discussionmentioning
confidence: 98%
“…53 The I/R also increases the release of NF-kb in the kidney tissue. 54,55 In one study, it was shown that captopril application inhibited the NF-kb signal pathway and decreased the TNF-a and iNOS. 56,57 Therefore, ACE inhibitors and AT-2 antagonist inhibition can be used in preventing chronic complications induced by disease.…”
Section: Discussionmentioning
confidence: 99%